2022
DOI: 10.1097/sla.0000000000005768
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mortality and Reintervention After Endovascular and Open Abdominal Aortic Aneurysm Repairs in Australia, Germany, and the United States

Abstract: Objective: To examine long-term outcomes after endovascular (EVAR) and open repairs (OAR) for intact abdominal aortic aneurysms in Australia, Germany, and the United States, using a unified study design. Background: Similarities and differences in long-term outcomes after EVAR versus OAR across countries remained unclear, given differences in designs across existing studies. Methods: We identified patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Open versus endovascular treatment has been the subject of debate and a large multinational study demonstrated important similarities in long-term outcomes after endovascular and open aortic repairs across three countries Australia, Germany, and the United States [ 14 ]. Another study showed that both surgeries had high mortality, and 68.0% in the endovascular-repair group and 70.0% in the open-repair group died (hazard ratio, 0.96; 95% confidence interval [CI], 0.82 to 1.13).…”
Section: Discussionmentioning
confidence: 99%
“…Open versus endovascular treatment has been the subject of debate and a large multinational study demonstrated important similarities in long-term outcomes after endovascular and open aortic repairs across three countries Australia, Germany, and the United States [ 14 ]. Another study showed that both surgeries had high mortality, and 68.0% in the endovascular-repair group and 70.0% in the open-repair group died (hazard ratio, 0.96; 95% confidence interval [CI], 0.82 to 1.13).…”
Section: Discussionmentioning
confidence: 99%
“…A major disadvantage of endovascular therapy is the increased reintervention rate and long-term complications compared with OAR, which is not reflected by this data. This problem is not only known for endovascular therapy of TAAA but also for AAA and endovascular treatment of the aortic arch [ 21 , 22 ]. In the treatment of AAA, late complications after endovascular repair lead to better long-term survival for open surgery after an initial benefit of endovascular therapy [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This problem is not only known for endovascular therapy of TAAA but also for AAA and endovascular treatment of the aortic arch [ 21 , 22 ]. In the treatment of AAA, late complications after endovascular repair lead to better long-term survival for open surgery after an initial benefit of endovascular therapy [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%